2010
DOI: 10.1007/s11284-010-0692-4
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus acquisition and competitive abilities of two herbivorous zooplankton, Daphnia pulex and Ceriodaphnia quadrangula

Abstract: Contrary to an expectation from the size-efficiency hypothesis, small herbivore zooplankton such as Ceriodaphnia often competitively predominate against large species such as Daphnia. However, little is known about critical feeding conditions favoring Ceriodaphnia over Daphnia. To elucidate these conditions, a series of growth experiments was performed with various types of foods in terms of phosphorus (P) contents and composition (algae and bacteria). An experiment with P-rich algae showed that the threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
3
11
0
Order By: Relevance
“…Such an adaptation could give smaller Daphnia a competitive advantage, and (together with their lower vulnerability to visually hunting predators, Gliwicz 1969) can lead to their dominance over large-bodied species. This is consistent with the results of Iwabuchi and Urabe (2010), who demonstrated that small cladocerans such as Ceriodaphnia quadrangula can outcompete larger Daphnia pulex even in the absence of size-selective predation due to their greater ability to benefit from P-rich bacterial food. This is also consistent with the more recent finding by Iwabuchi and Urabe (2012) that the quality of food influences the competitive superiority of a herbivore zooplankton species in terms of threshold food levels.…”
Section: Discussionsupporting
confidence: 92%
“…Such an adaptation could give smaller Daphnia a competitive advantage, and (together with their lower vulnerability to visually hunting predators, Gliwicz 1969) can lead to their dominance over large-bodied species. This is consistent with the results of Iwabuchi and Urabe (2010), who demonstrated that small cladocerans such as Ceriodaphnia quadrangula can outcompete larger Daphnia pulex even in the absence of size-selective predation due to their greater ability to benefit from P-rich bacterial food. This is also consistent with the more recent finding by Iwabuchi and Urabe (2012) that the quality of food influences the competitive superiority of a herbivore zooplankton species in terms of threshold food levels.…”
Section: Discussionsupporting
confidence: 92%
“…It thus seems that consumer stoichiometry is not a useful predictor of arthropod responses to variation in resource nutrient content. We note that theories on ecological stoichiometry like the growth rate theory, which relates body P content to the RNA content and indirectly to individual growth rates [35], focused originally on aquatic species under P-saturated conditions and the growth rate theory has mainly been applied in aquatic systems, notably on Daphnia [27], [37], [55][57], but see [10].…”
Section: Discussionmentioning
confidence: 99%
“…P-deficient diets can cause a significant drop in body P content of Daphnia (DeMott et al 1998) and inhibit its growth and reproduction (Schulz & Sterner 1999;DeMott et al 2001;Weider et al 2004). Several investigators also observed that the P content of algal food can affect the threshold food concentration of cladocerans (Boersma & Kreutzer 2002;Iwabuchi & Urabe 2010) and determine their growth rates. However, the growth and fecundity of Bosmina with lower body P content were not affected by the P content of algal food (Schulz & Sterner 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the growth of Daphnia is determined by the availability and quality of food (Acharya et al 2004) and phosphorus (P) concentration is a key aspect of food quality for freshwater zooplankton (Gulati & DeMott 1997). Iwabuchi and Urabe (2010) found that the P content of algae affects the threshold food level of cladocerans at which an individual's growth rate equals zero and that the somatic growth rate of Daphnia is higher when the animal is fed P-rich food. Other studies have shown that cellular P content can affect the growth and reproduction of cladocerans under phosphate deficiency condition (Schulz & Sterner 1999).…”
Section: Introductionmentioning
confidence: 99%